Civilisational conflict, renewal or transformation: potential role of the OIC - Ahsan, Abdullahil (International Institute of Advanced Islamic Studies Malaysia (IAIS), 2013)
The Organization of Islamic Cooperation (OIC) came into existence at the end of the 20th century during the Cold War, a period that also witnessed concerns among many Western intellectuals about the decline of the West. By the end of the century and the collapse of the former Soviet Union, the “clash of civilizations” thesis had placed Islamic civilisation at the center of international politics, once again raising questions about world peace and coexistence between civilisations. Could Islamic civilisation as represented by the OIC play a role at this juncture of history? Does it possess the capacity and know-how to meet this challenge? Such questions relate also to ideas of worldview: the Renaissance worldview of the West may be seen to have been tainted by Darwinism and Freudianism while the Islamic worldview appears corrupted by extremism. Can the OIC revive the universal Islamic values such as those upheld by Muhammad Iqbal – the 20th century student of Rumi? Can it do so in the context of tumultuous intra-Muslim relations? These questions frame our discussion in this paper.